Ultrasound-guided thoracic paravertebral block in a premature neonate with congenital oesophageal atresia with a tracheo-oesophageal fistula: a case report - Faruk Çiçekci (Cukurova Medical Journal, 2022)
Ultrasound-guided thoracic paravertebral block (TPVB) is a promising new technique for use in children of various ages. In this case report, a successful ultrasound (USG) guided TPVB procedure in premature neonate is described. A 3-day-old 1600-g neonate, born at 32 weeks of gestation, was underwent thoracostomy for esophageal atresia with esophageal fistula repair. At the end of the surgery, USG-guided TPVB were successfully performed using a linear probe in the paramedian position. USG-guided TPVB could be an alternative method for providing effective analgesia in a premature neonates in the future.